The Enforcement of Collective Bargaining - Brinker, Paul A. (Quarterly Journal of Economics, 1948)
Journal Article The Enforcement Of Collective Bargaining Get access Paul A. Brinker Paul A. Brinker University of Oklahoma Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 62, Issue 2, February 1948, Pages 314–322, https://doi.org/10.2307/1883225 Published: 01 February 1948